1987
DOI: 10.1139/g87-151
|View full text |Cite
|
Sign up to set email alerts
|

Karyological identification of two taxa of the Anopheles balabacensis complex from Burma

Abstract: Giemsa and Hoechst staining of neuroblast chromosomes were used to identify two strains of the Anopheles balabacensis complex from Burma. The laboratory colony of Kwan-ka-thaung (KKT) strain is shown to correspond to A. dirus A, while the laboratory colony of Taikkyi (TKK) strain corresponds to A. dirus C as defined by earlier studies on material from Thailand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…at site 49 [36] and 148 [37], and An. scanloni at site 126 [37], should be taken with caution and investigated further. This is also the case for records of An.…”
Section: Resultsmentioning
confidence: 99%
“…at site 49 [36] and 148 [37], and An. scanloni at site 126 [37], should be taken with caution and investigated further. This is also the case for records of An.…”
Section: Resultsmentioning
confidence: 99%
“…Several crossing, chromosomal, and RFLP studies confirmed the species status of An. scanloni (Baimai et al 1984a;1987;1988a;May 1987;Baimai 1988aBaimai , 1988bYasothornsrikul et al 1988;Sawadipanich et al 1990;Audtho et al 1995;Poopittayasataporn & Baimai 1995). Scanning electron micrographs of the eggs of An.…”
Section: Anopheles (Cellia) Scanlonimentioning
confidence: 99%
“…Anopheles dirus species C of Baimai et al ., 1984: 536 (cytogenetics); Wibowo et al ., 1984: 425 (H‐banding pattern of sex chromosomes); Baimai et al ., 1987: 157 (crossing, chromosomes); May, 1987: 886 (neuroblast chromosomes); Baimai, 1988a: 13 (heterochromatin, evolution, distribution); Baimai, 1988b: 667 (population cytogenetics); Baimai et al ., 1988d: 372 (polytene chromosomes); Yasothornsrikul et al ., 1988: 703 (RFLP); Damrongphol & Baimai, 1989: 563 (egg morphology); Peyton, 1990: 197 (taxonomy); Sawadipanich et al ., 1990: 477 (cytogenetics, crossing, evolution); Green et al ., 1992: 29 (enzyme electromorphs); Audtho et al ., 1995: 107 (DNA hybridization); Poopittayasataporn & Baimai, 1995: 426 (polytene chromosomes, phylogeny); Walton et al ., 1999: 24 (ASA PCR species identification); Walton et al ., 2000: 962 (mtDNA genetic structure); Walton et al ., 2001: 569 (population genetics, microsatellites); Huong et al ., 2001: 615 (PCR species identification); Manguin et al ., 2002: 46 (SCAR markers, multiplex PCR).…”
mentioning
confidence: 99%
“…Several crossing, chromosomal and RFLP studies confirmed the species status of An. scanloni (Baimai et al ., 1984, 1987, 1988d; May, 1987; Baimai, 1988a, 1988b; Yasothornsrikul et al ., 1988; Sawadipanich et al ., 1990; Audtho et al ., 1995; Poopittayasataporn & Baimai, 1995). Scanning electron micrographs of the eggs of An.…”
mentioning
confidence: 99%